1997
DOI: 10.1007/s11746-997-0256-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (Z)‐3‐hexen‐1‐yl butyrate in hexane and solvent‐free medium using Mucor miehei and Candida antarctica lipases

Abstract: Z)-3-Hexen-1-yl butyrate is an important flavor and fragrance compound as it represents the model of a natural herbaceous (green) note. Two immobilized lipases from Mucor miehei (Lipozym IM) and from Candida antarctica (Novozym 435) were investigated for their use in the synthesis of (Z)-3-hexen-1-yl butyrate by direct esterification in n-hexane. To determine optimal conditions for esterification, we examined the following parameters: temperature, amount of lipase, acid/alcohol ratio, and absence of solvent. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…The biocatalysis of ( Z )‐3‐hexen‐1‐yl butyrate by direct esterification was successfully achieved using lipases in n ‐hexane and in a solvent‐free system in a previous report 3. In our study the molar conversion of hexyl butyrate by direct esterification in n ‐hexane was higher than that in the solvent‐free system under the same reaction conditions.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The biocatalysis of ( Z )‐3‐hexen‐1‐yl butyrate by direct esterification was successfully achieved using lipases in n ‐hexane and in a solvent‐free system in a previous report 3. In our study the molar conversion of hexyl butyrate by direct esterification in n ‐hexane was higher than that in the solvent‐free system under the same reaction conditions.…”
Section: Resultssupporting
confidence: 60%
“…Carvalho et al 2 reported that hexyl acetate was synthesised by the cutinase‐catalysed transesterification reaction of butyl acetate with hexanol in a reversed micelle system. Bourg‐Garros et al 3 synthesised ( Z )‐3‐hexen‐1‐yl butyrate in high yield by direct esterification using Mucor miehei (Lipozyme IM) and Candida antarctica (Novozym 435) lipases in hexane and in a solvent‐free system.…”
Section: Introductionmentioning
confidence: 99%
“…Majumder et al [25] obtained a 100% molar conversion in case of benzyl acetate synthesis in 10 min using Lipozyme RM IM lipase and vinyl acetate as an acyl donor. In another study Bourg-Garros et al [26] reported 80% bioconversion yield of (Z)-3-hexen-1-yl butyrate in 4 and 6 h using M. miehi and C. antarctica lipases, respectively, under solvent-free conditions.…”
Section: Resultsmentioning
confidence: 99%
“…3 In our study the molar conversion of hexyl butyrate by direct esterification in n-hexane was higher than that in the solvent-free system under the same reaction conditions. Owing to its low toxicity and easy removal after the reaction, n-hexane was chosen as organic solvent in the optimal synthesis of hexyl butyrate by RSM.…”
Section: Results and Discussion Effect Of Solvent And Added Watermentioning
confidence: 41%